Fuzzy Topological Spaces: A Mathematical Tool for Studying Uncertainty and Vagueness - Shah, Yogendra Prasad (Patan Prospective Journal, 2022)
Fuzzy topological spaces are a type of mathematical structure that is used to study the behavior of systems that are not completely defined or certain. This type of space allows for the representation of uncertainty and vagueness within a system, and has been applied in various fields including computer science, engineering, and economics. This paper will provide an overview of fuzzy topological spaces and their applications in these fields.